Compositional Method in the Organization of Residential Quarters in Moscow and Leningrad in the Second Half of the 1920s — Early 1930s - Vasileva, Anna V. (Actual Problems of Theory and History of Art, 2022)
The article analyzes the characteristic compositional techniques in the construction of residential blocks of mass capital construction in Moscow and Leningrad. The transformation of approaches to their composition is caused by changes in state ideology and the economic situation. It is determined that the principles of allocation of land plots for new construction had a direct impact on the organization of residential areas. The difference in approaches to building the composition of a block is explained by the peculiarities of understanding the role of these objects in the formation of the urban fabric and their connection with the urban environment. It is shown that the Moscow practice is characterized by isolated design of residential complexes, almost without connection with the environment. But at the same time, there is a fairly pronounced functional zoning within these objects with front and courtyard spaces. The Leningrad practice from the very first examples was focused on creating a complete fragment of the urban fabric included into the environment. This inclusion occurs both from a compositional and functional point of view. At the same time, there is no functional zoning within the blocks. This is due to the different principles of organizing the layout of typical residential sections and the conditions for the arrangement of buildings on the site.